Facile synthesis of NiS2@MoS2 core–shell nanospheres for effective enhancement in microwave absorption. Issue 36 (24th April 2017) - Zhang, Xiao-Juan; Wang, Shan-Wen; Wang, Guang-Sheng; Li, Zhen; Guo, Ao-Ping; Zhu, Jia-Qiang; Liu, Da-Peng; Yin, Peng-Gang
Abstract : Core–shell structural NiS2 @MoS2 nanospheres have been successfully fabricated and they possess enhanced microwave absorption properties as compared to single NiS2 nanospheres or MoS2 nanoplates due to this core–shell structure. Abstract : Core–shell structured NiS2 @MoS2 nanospheres have been successfully fabricated via a facile hydrothermal method. The structure and morphology of the nanospheres were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The results indicated that this unique core–shell structure was beneficial to high-performance microwave absorption. A possible absorption mechanism was explained in detail. As an absorber, nanocomposites with a filler loading of 20 wt% exhibited enhanced microwave absorption properties due to characteristic impedance matching, synergistic effects, dipole and interface polarization, multiple reflections and quarter-wavelength matching. The minimum reflection loss can reach −41.05 dB at 12.08 GHz, and the absorption bandwidth exceeding −10 dB is 4.4 GHz with a thickness of 2.2 mm.